Red and White Porridge in the Suro Ceremony: Symbolism and Muslim Communal Integration in Martoba Village, North Siantar - Siti Mawaddah; Hasnah Nasution (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
Abstract: Purpose – The aim of this study is to identify the symbolic meaning of the bubur merah putih tradition in the Suro ceremony and to analyze its contribution to the integration of Muslims in Martoba Village. Design/methods/approach – This research employs a descriptive qualitative approach, using data collection techniques such as observation, interviews, and documentation. Findings – The findings reveal that the bubur merah putih tradition contains profound symbolic values. The red color symbolizes spirit, courage, and struggle, while the white color represents purity, sincerity, and heartfelt devotion. These symbolic meanings strengthen values of brotherhood, solidarity, and togetherness among community members. Furthermore, the implementation of this tradition fosters social harmony through collective participation in every stage of the ceremony. Conclusion – The bubur merah putih tradition in the Suro ceremony is not only culturally and religiously significant but also holds a social function in strengthening the integration of Muslims in Martoba Village. Research Implications – This research provides insights into the role of local traditions in maintaining social cohesion and religious harmony. It emphasizes the importance of preserving cultural rituals as a medium for fostering integration, unity, and mutual respect in plural communities.